Collections and services of public libraries in West Bengal, India: An evaluative study against the backdrop of the IFLA guidelines. (June 2021) - Munshi, Shamim Aktar; Ansari, Mehtab Alam
The purpose of this study was to investigate the status of district-level public libraries in West Bengal, India. The study focused on staff as well as services against the backdrop of collection development policy. It also investigated the problems faced by librarians and suggested measures to overcome these difficulties. The researchers used a mixed-methods approach – quantitative and qualitative methods – to obtain the data. However, the primary means of data collection was a survey method using a structured questionnaire. Additionally, interviews were carried out with librarians in order to bring more subjectivity to the results. The findings suggest that no selection committees have taken place to recruit new staff in different public libraries; hence, libraries have been suffering from a shortage of staff. Due to severe shortage of library staff, book database has not been completed in Libsys library management software in any surveyed library. Public libraries are established to provide a variety of services to their users. Thus, services are the main product of the public library system. The findings reveal that different kinds of services – such as children's, career guidance and community information services – are provided by the surveyed libraries to benefit their user communities.